Asuhan Kebidanan Komprehensif pada Ny. R dengan Keluhan Nyeri Punggung (Low Back Pain) di Klinik Sejahtera Pekanbaru - Sri Rahayu; Nevi Susianty (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Back pain is a discomfort in pregnancy caused by shifting the center of gravity and changes in posture in pregnant women. One way to overcome it is by using warm compress therapy to reduce back pain in pregnant women. At the Prosperous Clinic implementing continuous care with calcium administration. The purpose of this midwifery care is to be able to carry out comprehensive and continuous midwifery care for pregnant women by giving warm compresses to reduce the intensity of back pain. The method used is a case study with midwifery care. In conclusion, care is carried out with warm compress therapy using buli-buli or bottles filled with warm water attached to the painful area 1x a day in the afternoon with a water temperature of 43-48 ?. The results of the evaluation of pain intensity measurements both before and after giving warm compresses proved to be effective to use and back pain has begun to decrease. It is hoped that each clinic can provide information on how to overcome back pain with therapy on handling back pain using warm compresses in pregnant women's classes.